Role of pathology in sub-Saharan Africa: An example from Sudan - Khalid Dafaallah; Awadelkarim; Ahmed Abdalla; et al (Dove Medical Press, 2010)
Khalid Dafaallah, Awadelkarim1, Ahmed Abdalla, Mohamedani2, Massimo Barberis31Department of Molecular Biology, National Cancer Institute, 2Department of Pathology, Faculty of Medicine, University of Gezira, Wad Medani, Sudan; 3Department of Pathology, European Institute of Oncology, Milan, ItalyAbstract: In sub-Saharan Africa there is an extreme shortage of pathology services and, when provided, they are of unacceptable standard. Specimen handling and storage are very poor, and render this important aspect of medicinal practice rudimentary. The situation on the ground reflects the full spectrum of the educational, cultural, political, and economical challenges that must be confronted in building basic scientific capabilities in the life sciences, including medicine, in such countries. It is a difficult and often discouraging situation, however, several constructive initiatives have been promoted to address this problem. In this paper we describe the current state of pathology services in sub-Saharan Africa, documenting our experience in Sudan. We also report some of the results obtained by others and our future goals, and propose how pathology-related problems could be addressed in sub-Saharan Africa, by focusing on specific critical points, which may also be considered for other developing countries outside Africa.Keywords: pathology, Africa, networks, standard operative procedures, telepathology